Left atrial hemodynamics and left ventricular remodeling –predictors of outcomes after Transcatheter mitral valve repair with the MitraClip device. Issue 1 (23rd September 2018) - Lazkani, Mohamad; Sawant, Abhishek C.; Taase, Alicia; Khan, Sahoor; Fang, Kenith; Iyer, Vijay; Pershad, Ashish
Abstract: Background: Increased afterload and reduced left ventricular (LV) performance are sequela of mitral valve repair. However, hemodynamic left atrial and ventricular parameters that can predict outcome following mitral valve repair remain elusive. Methods: One hundred and two consecutive patients undergoing MitraClip procedure from 2014 to 2017 at Banner University Medical Center were enrolled in this study. All patients underwent pre‐procedure echocardiograms and intra‐procedure invasive left atrial (LA) pressure monitoring. Clinical, laboratory, and procedural parameters were collected. The primary end‐point was the composite outcome of all‐cause mortality and repeat hospitalization within 90 days. Results: The mean age was 77 ±10 years, the majority were Caucasians (93, 91.2%) and 47 (46.1%) were males. Thirty‐two patients (31.4%) had diabetes, 39 (38.2%) had renal insufficiency, and 38 (37.3%) had a history of congestive heart failure. The median society of thoracic surgeons score was 6.7% (Interquartile range [IQR]: 3.9, 10.2). Immediately post‐procedure there was a significant reduction in the LA pressure (Mean 12.0 vs. 18.6 mmHg, P  < 0.001) and pulmonary artery systolic pressure (43.5 vs. 53.2 mmHg, P  = 0.001) compared to baseline. LA pressure was an independent predictor of the composite outcome in an unadjusted (OR = 1.07, 95% CI: 1.00–1.13, P  = 0.03) and adjusted (OR = 1.07, 95% CI: 1.00–1.14, P  = 0.03) analysis respectively. Conclusion: LA pressure drop is an independent predictor of outcome after the MitraClip procedure. This finding has implications for early identification of patients at risk of poor outcomes and instituting aggressive medical therapy and close follow‐up for avoiding hospitalizations for heart failure decompensation.